Pengembangan LKPD Kearifan Lokal Berbasis Augmented Reality untuk Meningkatkan Keterampilan Proses Sains dan Berpikir Kreatif : Systematic Literature Review - Dian Islamiyati; Mahrus; Joni Rokhmat; Yunita Arian Sani Anwar (Kappa Journal, 2024)
The science process skills and creative thinking skills of Indonesian students are still low, thus requiring innovation in the learning process. This research aims to analyze the impact of using local wisdom-based Augmented Reality Student Worksheets (LKPD) to improve students' science process skills and creative thinking skills. The research method chosen in this study is Systematic Literature Review (SLR). The data collection technique in this research is by identifying, reviewing, evaluating, and interpreting articles relevant to the publication period between 2019 and 2024 available in the Google Scholar database with relevant keywords. A total of 13 articles were found and have been evaluated based on inclusion and exclusion criteria. The results of this study indicate that the use of local wisdom-based augmented reality LKPD that has been developed can improve students' science process skills and creative thinking skills. The local wisdom-based augmented reality LKPD that has been developed has been proven to be valid, practical, and effective for use in the learning process